Operational Leadership - Spanyi, Andrew (Business Expert Press, 2010)
Ebook from IG Library ; Relying on concepts introduced by Dr. John Kotter, Dr. G. Rummler & Alan Brache, Dr. Tom Davenport, and Dr. Michael Hammer, this new book updates this body of knowledge and presents a framework for action in an easy to read, actionable format. It's an outstanding title that provides details on the demand for the new operational leadership mindset and paradigm which enables both breakthrough change and the discipline of continuous improvement in operations.